Comportamiento de dos tipos de alcohol en la obtención de aceite útil a partir de residuos aceitosos de pescado en CIESA. - Cedeño Vargas, María Belén (2018)
The objective of this research was to determine the effectiveness of two alcohols (ethanol and methanol) in the oil extraction process, from the oily waste generated as a consequence of the pre-treatment of CIESA wastewaters (Conservas Isabel Ecuatoriana SA) in the city of Manta, and promote the use of oil as raw material to produce biofuel. A sampling of 8 hours a day for 12 days was considered and for extraction three concentrations were used in the two types of alcohol: 45%, 75% and 95%. The main response variable to evaluate was the volume of oil extracted, to then analyze specific parameters that would allow determining the best treatment. 72 oil samples were obtained with an average of 20,42 cm3 which represents 14% of the initial volume of the sample taken corresponding to 150 cm3, where the treatment with the best result corresponded to 95% ethanol with a value of 117 cm3 of extracted oil demonstrating with this a better effectiveness surpassing 50% of oil content in the initial residual sample, in spite of the positive results that were obtained it could be determined that there is no significant difference in the statistical analysis making it clear in this way that the alternative hypothesis is rejected and therefore the hypothesis becomes null.